Multiuser Based Savings And Loans Information System: (Case Study Of KSU " DANA MANDIRI " Mranggen Demak ) - Umi Kholifah; Candra Supriadi; Jarot Dian Susatyono (Journal of Engineering, Electrical and Informatics, 2023)
The increasingly rapid development of computer technology provides convenience for humans in carrying out life activities, this has resulted in the use of computers being an alternative taken by various agencies because it is considered to provide more advantages than disadvantages. Computers are tools to improve performance in various fields. In solving data processing problems at the KSU " DANA MANDIRI " Cooperative, based on the survey carried out, the author tried to change the manual or conventional data processing program into a computer-based data processing program, namely by using the Visual Foxpro 9.0 program. This change aims to provide comfort for operators in carrying out their work. With old programs, conventionally inputting data still takes a long time and when searching for data you still have to look for codes one by one because it cannot be done automatically. With these problems the author tries to formulate the problem, namely "How to make a data processing program to save borrow at KSU " DANA MANDIRI " using the Visual Foxpro 9.0 programming language. The savings and loan data processing process can be accessed quickly and precisely and provides a more attractive appearance. In solving this problem the author tried to collect data related to savings and loan data. In designing a new system, several stages are carried out including data design. Table creation, ERD creation, DFD and normalization. In processing the savings and loan data, it is hoped that it can help with problems that arise at the KSU " DANA MANDIRI " Cooperative and the program created of course still has several weaknesses and shortcomings, this is possible because the author still has little knowledge and experience in programming issues. Suggestions and criticism really help the author to further develop knowledge in this field.